Optimized extraction of phenolic compounds and antioxidant activity from cannabis Co-products via a combination of solvent-ultrasound-assisted extraction, response surface methodology, and sensitivity analysis - Maryem El Oihabi; Mohammed Soultana; Imad El Fellah; Hajar Fakih Lanjri; Laïla Ben Allal; Mohammed Ammari; Asmaa Fakih Lanjri (Case Studies in Chemical and Environmental Engineering)
This study aimed to optimize the extraction conditions of total polyphenols, flavonoid contents, and DPPH-IC50 from the stem part of Moroccan cannabis via a multidimensional approach. The response surface methodology and Box–Behnken design were used for the optimization based on sonication time, temperature, and ethanol concentration. Results showed that optimal response values were 125 mg GAE/g for TPC, 81 mg QEq/g for TFC, and 17 μg/mL for DPPH-IC50. This study presents new data on the quantity of chemicals in the stem of Cannabis depending on extraction conditions, which is very important in the valorization of this green material. The established conditions provide a foundational framework for real-world applications in the extraction of bioactive compounds from Cannabis stems and other vegetal materials. However, more investigations are needed to identify the molecules in the optimized extract.